The exercise of prosecutorial discretion during preliminary examinations at the International Criminal Court - Olugbuo, Benson Chinedu (Department of Public Law, 2017)
This study explores the exercise of prosecutorial discretion during preliminary examinations at the International Criminal Court. The key questions it investigates are whether there is a secure legal and theoretical basis upon which such discretion can and should be exercised and whether the Prosecutor of the International Criminal Court understands, develops and applies appropriate rules governing such discretion consistently. The study involves the analysis of various primary and secondary sources of law regulating the exercise of prosecutorial discretion. It begins by looking at the exercise of discretion at the national and international judicial systems to understand how their practices have informed and influenced the International Criminal Court Prosecutor, and then examines the provisions of the Rome Statute and its rules of evidence and procedure to determine the scope of the exercise of prosecutorial discretion. It also critically reviews the policy paper on preliminary examination adopted by the International Criminal Court Prosecutor. The study argues that, although the International Criminal Court Statute does not provide clear guidance on the exercise of prosecutorial discretion during preliminary examinations, there is a sufficient legal and theoretical basis upon which to exercise this discretion during preliminary examinations at the International Criminal Court. Article 42 of the Statute of the International Criminal Court, which provides for the independence of the Office of the Prosecutor is one such legal and theoretical basis. Thus, the Rome Statute clearly endorses the theory of prosecutorial neutrality. After expounding such a legal and theoretical basis, the thesis examines six case studies which represent six preliminary examinations conducted by the International Criminal Court Prosecutor in the conflicts in Uganda, Sudan, Côte d'Ivoire, Central African Republic, Kenya and Libya. The examination will answer the question whether the Prosecutor has exercised discretion in accordance with the spirit of the International Criminal Court Statute, and in a manner that would assuage claims that the Court is not neutral, especially in its dealing with African states. The analysis of these case studies shows that the Prosecutor has not exercised its discretion consistently and in a manner that can inspire public confidence in the administration of international criminal justice. To remedy this situation, the study recommends, among other things, the need for clarity on the exact roles of the Prosecutor and Pre-Trial Chambers during preliminary examinations, beyond the current practice where the Pre-Trial Chamber can only authorise the opening of proprio motu investigations. Second, the study recommends the review of the policy on the gravity of crimes. Although the policy paper on preliminary examination has clarified the fact that gravity involves both quantitative and qualitative analysis of victims of international crimes, it is not yet clear how to carry out gravity analysis. Third, the study proposes enhancing positive complementarity during preliminary examinations in order to encourage national efforts in the investigation and prosecution of international crimes. Finally, the study recommends that the decision to suspend or defer investigations or prosecutions in the 'interests of justice' under article 53 of the Rome Statute should be a shared responsibility between the Court and the United Nations Security Council.